Aplikasi Technology Acceptance Model (TAM) Terhadap Niat Menggunakan Personal Computer (PC) Tablet - Prakasa, Cokorda Bagus Aditya; Sri Ardani, I Gusti Agung Ketut (E-Jurnal Manajemen, 2013)
This study aimed to determine the effect of perceived usefulness, perceived ease of use, perceived benefits, and perceived costs simultaneously and partially on the intention to use and to know the variables that have a dominant influence. The samples used were 140 respondents to the purposive sampling technique. Multiple linear regression analysis is used as a data analysis technique. The results showed that perceived usefulness, perceived ease of use, perceived benefits and perceived costs simultaneously significant effect on intention to use the PC Tablet. In partial, perceived usefulness, perceived ease of use, and perceived benefits of a positive and significant effect while the perceived costs of a negative and significant effect on the intention to use the PC Tablet. The results shown indicate that the perceived benefits is variable dominant influence. Keyword: perceived usefulness, perceived ease of use, perceived benefits, perceived costs, intention to use